The investigation of the physical conditions of the printing environment on the ink colour value - (:unkn) unknown (My University, 2007)
The physical conditions of the printing environment are the most important factors on the quality of the printed image. The humidity in the printing room would affect the physical deformation of the printing paper during the printing and after the printing operation, in accordance with the humidity level whether it is high or low than the optimized conditions. On the other hand, the dryring problems arise in the printing operation using the printing inks which dry physically either by the penetration into the paper or by the absorption. Especially, uncoated hygroscopic papers absorb the humidity in the environments containing high level of humidity and they resist the absorption of oil-based inks. In this work, the uncoated white paper of 70 g/m2 was used as a test printing paper. The relative humidity of the printing room was setup at different values, between 50% and 70% and the changes in the humidity level of the paper was calculated. In each 10% increase in the humidity, the solid printings were carried out by an oil-based ink using the IGT Printing Test Instrument. The changes in the solid-tone densities were measured by Gretag D19C reflection densitometer during the printing and also 1, 3 and 24 hours later after the printing. In addition, the reflectance values of the test prints were measured by the use of Gretag Macbeth SpectroEye spectrophotometer, and CIE Lab values were calculated. It has been investigated that the humidity of the printing environment has affected the humidity content of the paper, the penetration of the inks into paper and also the colour shade of the prints.
Keywords: Adhesion; Densitometer; Density; Humidity; Spectrophotometer